2018
DOI: 10.1136/bjophthalmol-2018-313212
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopaenia as a predictor of sarcoidosis in patients with a first episode of uveitis

Abstract: Background/aimsThe diagnostic properties of conventional diagnostic tests (ACE and chest radiography) for sarcoidosis-associated uveitis are not ideal. The diagnostic value of lymphopaenia for sarcoidosis-associated uveitis is investigated.MethodsA retrospective study of 191 consecutive patients with a first uveitis episode visiting the ophthalmology department (Erasmus Medical Center, Rotterdam, The Netherlands). Receiver operating characteristics (ROC) analysis was performed and compared with known ROC value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…28 Based on a study of 191 patients with a first uveitis episode, Groen-Hakan et al found that lymphopaenia was strongly associated with a diagnosis of sarcoidosis, with an optimal cut-off of 1.47×10 9 /L, a strong sensitivity of 75% and a specificity of 77%. 15 Their study excluded patients undergoing immunosuppressive therapies. In our study, we found a low sensitivity of 15.3% which may be explained by the fact that we used a lower cut-off of 1.0×10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Based on a study of 191 patients with a first uveitis episode, Groen-Hakan et al found that lymphopaenia was strongly associated with a diagnosis of sarcoidosis, with an optimal cut-off of 1.47×10 9 /L, a strong sensitivity of 75% and a specificity of 77%. 15 Their study excluded patients undergoing immunosuppressive therapies. In our study, we found a low sensitivity of 15.3% which may be explained by the fact that we used a lower cut-off of 1.0×10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, large studies investigating lymphopaenia's value in predicting sarcoid uveitis remain scarce. [15][16][17] This study was conducted to investigate the value of lymphopaenia and elevated sACE, singly or in combination, as diagnostic biomarkers of sarcoid uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…97 When adjusted for sex, ethnicity and age of onset of uveitis, lymphopenia (<1.5 Â 10 9 / L) was found to be associated with a 12-fold increased risk of sarcoid uveitis. 98…”
Section: Lymphopeniamentioning
confidence: 99%
“…Two studies have investigated the diagnostic value of lymphopenia (<1 Giga/L) as a marker of sarcoidosis in patients with de novo uveitis. 80,81 First Jones et al showed that lymphopenia was predictive of sarcoidosis in 31% of uveitis patients. 80 More recently, Groen-Hakan et al reported a sensitivity and a specificity of lymphopenia for the diagnosis of sarcoidosis of 75 and 77%, respectively.…”
Section: Traditional Approachmentioning
confidence: 99%
“…80 More recently, Groen-Hakan et al reported a sensitivity and a specificity of lymphopenia for the diagnosis of sarcoidosis of 75 and 77%, respectively. 81 Lymphopenia resulted in a 12-fold increased risk for having sarcoidosis, corrected by sex, ethnicity, and age at onset of uveitis. Several studies have suggested that bronchoalveolar lavage (BAL) fluid analysis may be useful for the diagnosis of sarcoidosis, even with normal chest imaging, 82,83 but bronchial biopsies are usually negative in this situation.…”
Section: Traditional Approachmentioning
confidence: 99%